2021
DOI: 10.29036/jots.v12i23.274
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Domestic Tourism by Enhancing the Practice of Alternative Tourism as a Quality Measure to Satisfy and Retain National Tourists

Abstract: This study aims to study the satisfaction of national tourists with the tourism experience in the Sahara. It also seeks to examine the influence this has on the intention to return and spread positive word-of-mouth about this destination, work on its improvement to capitalize on the internal mobilities induced by COVID-19, and build a long-term relationship with them to strengthen regional attachment. Data were collected from 123 national tourists in Algeria using convenience sampling. Two analyses were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The operationalization of destination loyalty typically included scale items referring to recommendation or positive word-of-mouth (WOM) about the destinations, combined with other revisit intentions items within the same loyalty construct. However, some investigations specified and operationalized tourists’ recommendations or endorsements as additional, separate constructs in their models (e.g., Chebli et al, 2021 ; Kralikova et al, 2021 ; Koç et al, 2022 ; Suhartanto et al, 2022 ; Carvache-Franco et al, 2022a , b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The operationalization of destination loyalty typically included scale items referring to recommendation or positive word-of-mouth (WOM) about the destinations, combined with other revisit intentions items within the same loyalty construct. However, some investigations specified and operationalized tourists’ recommendations or endorsements as additional, separate constructs in their models (e.g., Chebli et al, 2021 ; Kralikova et al, 2021 ; Koç et al, 2022 ; Suhartanto et al, 2022 ; Carvache-Franco et al, 2022a , b ).…”
Section: Resultsmentioning
confidence: 99%
“…The model showed that the latter two constructs mediated the effects between public health service quality and destination loyalty. Chebli et al (2021) found tourists’ loyalty was determined by satisfaction (β = 0.688), which in turn was preceded by the perceived quality’s dimensions of physical/scenic environment (β = 0.233), relational environment (β = 0.213), entertainment (β = −0.881) and reliability/governance (β = 0.363) at the destination. Similarly, the research by Cambra-Fierro et al (2022) concluded that destination loyalty is explained by perceived quality (β = 0.660), which in turn is predicted by the destination’s image (β = 0.543) and perceived health safety (β = 0.194) producing indirect (mediation) effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that Instagram's graphical interface is primarily optimized for mobile devices and the user experience via other devices is less attractive. The presented results could be applied at the business level to improve the market position of enterprises through the use of modern technologies (Chebli et al, 2021;Hassan and Lee, 2021;Koľvekova et al, 2019;Kutlu and Ayyildiz, 2021;Mwatsika, 2021;Pereira-Moliner et al, 2021;Petrakova et al, 2021). Besides, the research framework could be applied in other areas (Gavurova et al, 2020a;Gavurova et al, 2020b;.…”
mentioning
confidence: 97%
“…The last element is essential in changing environmental conditions. An example of a factor that significantly could influence the perception of the brands, especially in the context of their social responsibility, is the period of the COVID-19 pandemic (e.g., the tourism sector) (Chebli et al, 2021).…”
mentioning
confidence: 99%